A COMPARATIVE STUDY OF ENGLISH LANGUAGE TEACHING METHODOLOGIES IN UPPER SECONDARY SCHOOLS AND MILITARY-ORIENTED LYCEUMS - Qakhramonova Dilorom Abdiaziz qizi (Bright Mind Publishing, 2025)
English is considered one of the most popular and widespread languages in the modern world. The process of teaching English in higher secondary schools and military-oriented lyceums is important in order to improve the quality of education in our country, make youth competitive in the international arena and train mature personnel in the military field. The methodologies for teaching English in these schools and lyceums have their own characteristics, each of which is characterized by its pedagogical approaches, goals and objectives. This article provides a comparative analysis of the peculiarities, advantages and disadvantages of the methodology of teaching English in these two types of educational institutions.
Keywords: English, knowledge, skills, speaking, writing, reading skills, education, lesson, analysis.